Réponse :
Explications étape par étape
Bonjour
Soient x, y et m trois réels. Factoriser les expressions littérales suivantes.
1. x(x-2)+(x-1)x
= x(x - 2 + x - 1)
= x(2x - 3)
2. 2x(x + y) + 4x(y2 +1)
= 2x(x + y + 2(y^2 + 1))
= 2x(x + y + 2y^2 + 2)
= 2x(2y^2 + x + y + 2)
3. (7-m)(m+1)-(7-m)(3m-1)
= (7 - m)(m + 1 - 3m + 1)
= (7 - m)(-2m + 2)
= (7 - m) * 2(-m + 1)
= 2(7 - m)(-m + 1)
4. (2x+3)2 – (2x+3)(x-5)
= (2x + 3)(2x + 3 - x + 5)
= (2x + 3)(x + 8)
5. (7y+3)2 – 25
= (7y + 3)^2 - 5^2
= (7y + 3 - 5)(7y + 3 + 5)
= (7y - 2)(7y + 8)